Phenotypic and genotypic identification of Aeromonas spp. isolated from a chlorinated intermittent water distribution system in Lebanon - Tokajian, Sima (2004)
Aeromonas spp. were detected in samples collected from both untreated groundwater and treated drinking water in Lebanon. Aeromonas spp. levels ranged between 2 and 1,100 colonies per 100 ml in the intake underground well and between 3 and 43 colonies per 100 ml in samples from the distribution system. Samples positive for Aeromonas spp. from the network had a free chlorine level ranging between 0 and 0.4 mg l −1. Multiple antibiotic-resistance was common among the isolated aeromonads; all were resistant to amoxycillin while 92% showed resistance to cephalexin. Haemolysis on blood agar was detected in 52% of the isolates recovered from the distribution network and 81% of isolates from the untreated underground source. The Biolog microbial identification system assigned identities to all of the isolated presumptive aeromonads (at least at the genus level), which was not the case with the API 20NE strips. Differences at the species level were observed when results from the Biolog system were compared with identification based on the MicroSeq 500 16S rDNA sequence analysis. The presence of Aeromonas spp. in drinking water can be an important threat to public health, thus greater awareness of Aeromonas strains as potential enteropathogens is warranted.